A Comparative Study of Abuddin Nata and Naquib Al-Attas's Concepts of Character Education Values - Rahimah, Riska Siti; Yuliharti; Alwizar (JIE (Journal of Islamic Education), 2025)
This study aims to analyze the conceptual comparison of character education values from the perspectives of Abuddin Nata and Naquib Al-Attas and to examine the relevance of integrating both perspectives for 21st-century Islamic Religious Education learning. The gap between the practical success of Islamic Religious Education in character formation and the theoretical idealism that emphasizes the need for deep philosophical foundations underscores the urgency of this research. The research method employs a qualitative approach with comparative-descriptive library research, data collection techniques through documentation of primary and secondary sources, data analysis using the Miles, Huberman, and Saldana model comprising data condensation, data display in comparison matrices, and conclusion drawing, as well as data validity testing through source triangulation and peer debriefing. The research findings indicate that Abuddin Nata develops character education values through a practical-pedagogical approach emphasizing noble character with strategies of role modeling, habituation, and curriculum integration. In contrast, Naquib Al-Attas develops a philosophical-epistemological approach that emphasizes the concepts of ta'dib and adab through worldview transformation and the understanding of the hierarchy of knowledge in Islam. The integration of both perspectives produces a comprehensive framework that bridges the gap between practical success and theoretical ideality, thereby deepening students' metaphysical awareness through Al-Attas's philosophical foundation. In contrast, Nata's practical strategies ensure effective implementation in Islamic Religious Education. The relevance of this integration contributes significantly to achieving SDG 4 on quality education by fostering strong character as a foundation for sustainable development grounded in universal and humanistic Islamic values.